(untitled) (Research, Society and Development, 2021)
Analyze the form and content of information about what is good for the voice, served on ten most accessed Google Platform sites. This descriptive research did not need to be referred to the University Ethics Committee. The platform chosen to search the data was Google, as it became the main internet search tool. On April 15, 2021, the Google platform was accessed the phrase "what is good for the voice" was inserted for data search. At that time, the registration of approximately 142,000,000 results was made, and the ten links of the first page were selected. The findings were presented in numerical form and percentage. The results indicate that the sites use words that are easy to understand (100%), point to the importance of eating apple (90%) and liquids (90%) and warn against milk and derivatives (30%), and do use of screams and whispers (50%). It was concluded that these sites portray information present in the literature. However, aspects related to general health should be highlighted and related to voice production.